Global, regional, and national burden and quality of care index of liver cirrhosis by cause from global burden of disease 1990–2019. Issue 1 (8th November 2022) - Gorgani, Fateme; Esfahani, Zahra; Ghamari, Seyyed‐Hadi; Ghasemi, Erfan; Azadnajafabad, Sina; Shobeiri, Parnian; Mohammadi, Esmaeil; Moghaddam, Sahar Saeedi; Abbasi‐Kangevari, Mohsen; Fattahi, Nima; Tehrani, Yeganeh Sharifnejad; Farzi, Yosef; et al.
Abstract: Background and Aim: Cirrhosis and other chronic liver diseases are complex disorders with a known burden. Currently health systems have different approaches to dealing with this issue. The objective of this study is to describe the burden attributed to and quality of care for cirrhosis and other chronic liver diseases. Methods: Data of cirrhosis and other chronic liver diseases extracted from Global‐Burden‐of‐Diseases 2019. Four indicators, including mortality to incidence ratio, prevalence to incidence ratio, disability‐adjusted‐life‐years (DALYs) to prevalence ratio, and years‐of‐life‐lost (YLLs) to years‐lived‐with‐disability (YLDs) ratio, were defined and combined by the principal‐components‐analysis to construct the Quality‐of‐Care‐Index (QCI). Results: The global QCI of cirrhosis increased from 71.0 in 1990 to 79.3 in 2019. The QCI showed a favorable situation in higher SDI countries compared with lower SDI countries, with a QCI of 86.8 in high SDI countries and 60.1 in low SDI countries. The highest QCI was found in Western Pacific Region (90.2), and the lowest was for African Region (60.4). Highest QCI belonged to the 50–54 age group (99.5), and the lowest was for the 30.34 age group (70.9). Among underlying causes of cirrhosis, the highest QCI belonged to alcohol use, followed by hepatitis C and NAFLD with QCIs of 86.1, 85.3, and 81.1. Conclusions: There was a considerable variation in the QCI of cirrhosis and other chronic liver diseases. Countries with low QCI, mainly located in developing regions, need organized action to control the burden of cirrhosis and its underlying causes and improve their quality of care.